“People Would Just Say, ‘That Doesn’t Exist’”: An Analysis of the Experiences of Racialized International Students as Settler Colonial, Racial, and Gendered Violence - Park, Hijin; Francis, Margot (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2024)
A growing body of scholarship reveals that racialized international students in the West are disproportionately vulnerable to exploitation and violence on and off university and college campuses, and in public and private spaces. This harm may be due to the actions of individuals (such as landlords, employers, fellow international students, non-international student classmates, professors, strangers, and members of their ethnic communities), as well as the policies and inaction of institutions and governments. These institutional and systemic factors include precarious immigration status and visa and immigration requirements, unregulated homestay programs, unregulated tuition fees, and the intersections of racism, sexism, xenophobia, and Islamophobia. This paper draws on interviews with racialized international students and university employees who provide services to international students at a comprehensive university in Ontario, Canada, and argues that the everyday and structural violence the students may face is best understood as constitutive of the violence of White settler colonialism.